Determination of platinum group elements (PGE) in soil and grass using ICP-MS in UKM Engineering Lake - RINDI G. HATIKA (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2014)
Three elements in platinum group elements (PGE) which are platinum (Pt), palladium (Pd) and rhodium (Rh) are widely used in vehicle exhaust as catalyst in changing material and toxic gases such as CO, HC and NOx. However, the release of vehicle exhaust emission has increased the content of platinum group elements in the environment including dust, soil, water and grasses and sediments. The research aimed to determine the PGE content in grass and soil and to determine the concentration of Pt, Pd and Rh metals obtained in samples. The research was done at 4 station at UKM Engineering Lake, Malaysia. Analysis was done using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). Result of the research showed that Rh metal was present at grass and soil sample. The Rh metal concentration in grass sample is between 1. 770 µg/g to 15.225 µg/g and in soil sample is between 2.347  µg/g to 9.579  µg/g. Pt and Pd were not detected in all samples and all stations. There are 80 other elements detected in the analysis. However, only four elements were taken into consideration which were Cu, Zn, Ni and Pb Since these elements were originated from vehicles activities. Their presence showed that Rh metal detected was from catalyzed changer in vehicles